2020
DOI: 10.21203/rs.3.rs-16303/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Side effects--part of the package”: A mixed methods approach to study adverse events among patients being programmatically treated for DR-TB in Gujarat, India

Abstract: BackgroundHigh rates of Adverse Events (AEs) during treatment is one of the leading causes of unsuccessful treatment outcomes among patients with drug resistant tuberculosis (DR-TB). However, information related to AEs is not systematically collected and managed under programmatic setting. The present study assessed the a) incidence and pattern of adverse events in first three months of DR-TB treatment initiation; b) treatment seeking behaviour for AE management; and c) explore the challenges in seeking treatm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Less than half the numbers of clinicians and DOT-nurses were found to have been trained on aDSM component. This means very few health care workers had awareness on adverse events management, recording and reporting; a finding coherent with a study conducted in Namibia [15].Similar findings were seen in a study done India where it was reported that lack of training in AE management resulted in health care workers not knowing what, when or why they should report the adverse events occurring to the patients they attended [14]. The low number of trained staff in these findings could be attributed by the limited funds allocated for pharmacovigilance activities and high staff turnover among departments in the health facilities.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Less than half the numbers of clinicians and DOT-nurses were found to have been trained on aDSM component. This means very few health care workers had awareness on adverse events management, recording and reporting; a finding coherent with a study conducted in Namibia [15].Similar findings were seen in a study done India where it was reported that lack of training in AE management resulted in health care workers not knowing what, when or why they should report the adverse events occurring to the patients they attended [14]. The low number of trained staff in these findings could be attributed by the limited funds allocated for pharmacovigilance activities and high staff turnover among departments in the health facilities.…”
Section: Discussionsupporting
confidence: 68%
“…These results are similar to a study done in Tanzania where implementation of aDSM was found to be difficult since most health facilities either lacked the necessary toxicity monitoring equipment like ECG, or had been faulty or HCWs were unable to operate it [13]. Another similar study conducted in India, on adverse events among patients being programmatically treated, found that guidelines, SOPs and aDSM forms were available at the treatment centre; however some toxicity monitoring tests were not done due to absence of machines for the respective tests [14]. With facilitation of toxicity monitoring tests being far from adequate, the program should increase number of functional laboratories at least one laboratory in each district; rather than having just the Muhimbili national laboratory to serve all health facilities in Dar es Salaam region.…”
Section: Discussionmentioning
confidence: 99%